A fractal analysis method to characterise rock joint morphology. Issue 1 (August 2021) - Guida, G.; Casini, F.; Viggiani, G.M.B.
Abstract: Rock joints morphological characteristics strongly influence the shear strength dilatancy response of the discontinuity. Morphological features of rock joints are commonly identified with a roughness descriptor along standard 100 mm-length profile detected by instrumentation such as profilometers. This work extends a method proposed for fractal analysis of particle contours to describe rock joint profiles in terms of quantitative descriptors of their roughness. It is well-established that natural surfaces have a fractal nature, self similar over a wide range of scales. This implies that the measured length of their outline is a function of the measurement scale: the smaller the measurement scale, the longer the profile length. Based on the interpretation of the fractal analysis of rock joint profiles, relating the length of the profile to the measurement scale, descriptors identifying the roughness and its characteristic scale are proposed. The method is first applied to some artificial profiles, and later to real rock joint profiles.